Automatic Control Systems Modeling by Volterra Polynomials - S. V. Solodusha (Моделирование и анализ информационных систем)
The problem of the existence of the solutions of polynomial Volterra integral equations of the first kind of the second degree is considered. An algorithm of the numerical solution of one class of Volterra nonlinear systems of the first kind is developed. Numerical results for test examples are presented.